Satzglieder, Kasus und semantische Rollen: eine Einführung - Engels, Eva; Vikner, Sten (Tidsskrift for Sprogforskning, 2006)
Section 1 introduces the three concepts grammatical function, case and semantic role. Using examples from German and Danish, it is shown in section 2 that although these concepts have certain links to one another, there are no strict correlations between them. Section 3 shows that this is also the case in languages with a much richer case system, such as Finnish.